Investigation and modeling of various influencing factors on the dielectric breakdown strength of silicone elastomers - Ziegmann, Andreas; Berner, Claus; Schubert, Dirk W. (Nordic Polymer Days 2018, 2018)
Dielectric elastomers are utilized as soft electroactive polymers for actuators, sensors or generator applications to transduce mechanical to electrical energy and vice versa. They are characterized by the ability to change shape while an electrical field is applied. Indeed, this effect is most significant for electrical fields near the electrical breakdown strength, therefore it is a limiting factor for application. This work investigates different factors influencing the dielectric breakdown strength of soft silicone elastomers such as the sample thickness, the force and the radius of the upper electrode, the filling degree and the size of air voids. It can be shown that the main influence is the compression of the sample, thus a novel master curve can be created and fitted by a semi empirical model function. Therefore a comparison of all different experimental set-ups is possibl